Evaluation of in-situ shrinkage and expansion properties of polymer composite materials for adhesive anchor systems by a novel approach based on digital image correlation. (October 2019) - Singer, Gerald; Sinn, Gerhard; Lichtenegger, Helga C.; Veigel, Stefan; Zecchini, Michele; Wan-Wendner, Roman
Abstract: The curing reaction of thermosetting resins is associated with chemical shrinkage which is overlapped with thermal expansion as a result of the exothermal enthalpy. Final material properties of the polymer are determined by this critical process. For adhesive anchor systems the overall shrinkage behavior of the material is very important for the ultimate bond behavior between adhesive and the borehole wall. An approach for the in-situ measurement of 3-dimensional shrinkage and thermal expansion with digital image correlation (DIC) is presented, overcoming the common limitation of DIC to solids. Two polymer-based anchor systems (filled epoxy, vinylester) were investigated and models were developed, showing good agreement with experimental results. Additionally, measurements with differential scanning calorimetry (DSC) provided supporting information about the curing reaction. The vinylester system showed higher shrinkage but much faster reaction compared to the investigated epoxy. Highlights: In-situ shrinkage measurement of polymer composites via digital image correlation (DIC). Optical measurement of 3-dimensional deformations during phase change. Modelling of coupled chemical shrinkage and thermal expansion.